Complement activation and complement control proteins in acute pancreatitis. Issue 11 (November 1982) - Whicher, J T; Barnes, M P; Brown, A; Cooper, M J; Read, R; Walters, G; Williamson, R C
Abstract : Serum levels of the complement proteins C3, C4, C1 inhibitor (C1 INH), factor I (C3b inactivator) and factor H (BIH) and plasma levels of cleavage products of C3 (C3c) and factor B were measured in 26 patients with acute pancreatitis. Breakdown of C3 occurred in 19 patients, as shown by a reduction in C3 level and the presence of C3c. C4 levels, however, did not fall and factor B breakdown products were not detected, thus suggesting that enzymatic cleavage of C3 occurred without significant involvement of either the early classical pathway or the alternative pathway. C1 INH and factor H both showed increases, presumably reflecting an acute phase response. Factor I showed an initial fall followed by a rise. There was no correlation between the presence or extent of C3 breakdown and the clinical condition of the patients. It is concluded that C3 cleavage in pancreatitis probably results from tryptic activity and that the measurement of complement components has no part to play in the management of the disease.